Video transmission strategy in multi-rate and multi-node IEEE 802.11 networks - Liang CHEN; Xiang GU; Jin WANG (Tongxin xuebao)
The video transmission strategy VQCW (video queue contention window) was proposed for video transmission fair problem in multi-rate and multi-node IEEE 802.11 networks.The strategy was based on node queue selective packet drop and contention window dynamic adjustment.It deduced a maximum throughput model according to initial contention window size because of the relation between throughput and initial contention window size.This model can provide theoretical upper limit for improving throughput.The theoretical modeling and NS simulation show that the proposed strategy can maintain both video transmission quality and high network overall throughput.